The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/jmv.28161
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptome atlas reveals protective characteristics of COVID‐19 mRNA vaccine

Abstract: Messenger RNA (mRNA) vaccines are promising alternatives to conventional vaccines in many aspects. We previously developed a lipopolyplex (LPP)‐based mRNA vaccine (SW0123) that demonstrated robust immunogenicity and strong protective capacity against severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) infection in mice and rhesus macaques. However, the immune profiles and mechanisms of pulmonary protection induced by SW0123 remain unclear. Through high‐resolution single‐cell analysis, we found that SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Our study initially found that the newly constructed immune marker ICI has the potential to predict the progression of COVID-19 and the response to COVID-19-specific vaccines, and in the clinical setting, these findings can be effectively translated to some extent into the management of COVID-19 outbreaks, for example, an increasing number of studies have utilized gene expression to predict COVID-19 severity, which can provide a theoretical basis for the theoretical basis for prognostic management of COVID-19 patients [ [52] , [53] , [54] ]. In addition, the prediction of vaccine reactions can also be recognized [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study initially found that the newly constructed immune marker ICI has the potential to predict the progression of COVID-19 and the response to COVID-19-specific vaccines, and in the clinical setting, these findings can be effectively translated to some extent into the management of COVID-19 outbreaks, for example, an increasing number of studies have utilized gene expression to predict COVID-19 severity, which can provide a theoretical basis for the theoretical basis for prognostic management of COVID-19 patients [ [52] , [53] , [54] ]. In addition, the prediction of vaccine reactions can also be recognized [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, further research on the pathophysiological process and mechanism of occurrence and development of COVID-19 immunity is required. Recently, other cell types were also mentioned regarding the induction of trained immunity following a single dose of the ChAdOx1nCoV-19 vaccine and SW0123 vaccination effectively suppressed SARS-CoV-2-induced inflammatory responses by inhibiting the recruitment of proinflammatory macrophages and increasing the frequency of polymorphonuclear myeloid-derived suppressor cells using high-resolution single-cell analysis [ 27 , 28 ]. To reveal more mechanisms about COVID-19 vaccination, these conclusions need to be further clarified.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial component of mRNA therapy is the delivery system. Common delivery systems include protamine, lipoplex (LPX), 64 lipopolyplex (LPP), 65 virus-like particles (VLPs), 66 dendritic cell, 67 and LNPs. 68 Due to its most advanced status in current application, this review primarily focuses on the application of LNP technology.…”
Section: Delivery Platformsmentioning
confidence: 99%